Secondary hemostasis studies of crude venom and isolated proteins from the snake Crotalus durissus terrificus - Sousa, Ivancia D.L.; Barbosa, Ayrton R.; Salvador, Guilherme H.M. [UNESP]; Frihling, Breno E.F.; Santa-Rita, Paula H.; Soares, Andreimar M.; Pessôa, Hilzeth L.F.; Marchi-Salvador, Daniela P. (Elsevier, 2019)
Among the activities triggered by Crotalus durissus terrificus snake venom, coagulation is intriguing and contradictory since the venom contains both coagulant and anticoagulant precursor proteins. This work describes the in vitro effects of crude venom and purified proteins from snake Crotalus durissus terrificus as they affect coagulation factors of clotting pathways. Coagulant and/or anticoagulant activities of crude venom, and purified proteins were all analyzed directly in human plasma. Clots formed by crude venom and Gyroxin presented as flexible hyaline masses in punctiform distribution. Clot formation time evaluation of isolated proteins with PT and APTT assays made it possible to infer that these proteins interfere in all coagulation pathways. However, regarding ophidism by C. d. terrificus, Gyroxin acts directly, breaking down fibrinogen to fibrin and increasing the amount plasminogen activator, which results in the formation of thrombi. Crotoxin complex, Crotoxin A and Crotoxin B proteins can act in prothrombinase complex formation; Crotoxin B can inhibit prothrombinase complex formation by direct interaction with Factor Xa. Crotamine interacts with negatively charged regions of differing coagulation factors in all coagulation pathways, and possesses a whole set of activities causing dysfunction, activation and/or inhibition of natural anticoagulants and disturbing hemostasis.
Keywords: Activated Partial Thromboplastin Time; Anticoagulant proteins; Brazilian rattlesnake; Ophidism; Prothrombin Time